Development of Comic Based Learning on Reaction Rate for Learning to be More Interesting and Improving Student’s Learning Outcomes - Sri Adelila Sari*; Nur Fatni Amirah Harahap (Jurnal Pendidikan Sains Indonesia, 2021)
Teachers often use projector media in classroom learning. Rarely do they want to develop and vary learning media with the aim of making the learning process more interesting. Finally, the lack of student interest in reading textbooks results in low student learning outcomes, which are not the focus of teacher attention. This study was aimed to develop comic in the material on reaction rates. The method used was R D with ADDIE, namely analysis, design, development, implementation, and evaluation. The analysis stage was carried out by analyzing the needs in the form of student characteristics and identifying learning media. The media design stage included plot design, character design, and scenario creation. The design results were then developed at the development stage, then the comic was given to two validators to test their feasibility. The implementation phase was carried out at the XI IPA class XI IPA Senior High School LAB IKIP Al Washliyah Medan. Furthermore, student learning outcomes were measured at the evaluation stage using tests. The results of this study found that comic could be developed by meeting the eligibility criteria of 93.29 percent with very good criteria. Students were very enthusiastic about chemistry comic. Student learning outcomes obtained an average of 81.07, which means that the minimum completeness criteria value was 75. This study concludes that this chemistry comic learning media was very suitable for use in chemistry learning, especially in the material reaction rate and student learning outcomes were achieved good criteria.